Influence Discipline Work And Supervision To Employee Performance Through Work Achievements At The Regional Inspectorate Office Of Binjai City - Inggit Gemiasih; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2025)
Effective work discipline and supervision are expected to increase job satisfaction, which in turn has an impact on improving work performance. This study aims to analyze the effect of Work Discipline and Supervision on employee Work Performance mediated by job satisfaction at the Binjai City Regional Inspectorate Office. Data were obtained through a survey with a quantitative approach. And analyzed use method Partial Least Squares (PLS) with The number of samples was 107 employees. The results of the hypothesis test showed that work discipline and supervision had a positive and significant effect on work performance, with T-Statistics of 3.589 and 6.264 respectively, and P-Value <0.05. This shows that increasing discipline and supervision will improve employee work performance. In addition, work discipline and supervision also positively affect Job Satisfaction, with T-Statistic values of 5.266 and 4.842. Job Satisfaction is proven to have a significant positive effect on Job Performance, with a T-Statistic of 8.140, showing the important role of Job Satisfaction in driving employee performance. The results of the indirect effect test show that Supervision and Supervision have a significant effect on Job Performance through Job Satisfaction as a mediator. Indirect Effect of Work Discipline And Supervision to Performance Work through Satisfaction Work each has a T-Statistic of 4.920 and 3.637 > 1.96, and a P-Value < 0.05 < 0.05. This finding indicates that the influence of the two variables to Performance Work more effective when facilitated by high Job Satisfaction.